A Re-Examination of Earthquakes in Mediterranean Archaeology in Light of Historical Sources: The Case of Graeco-Roman Helike - Gaggioli, Amanda M. (Journal of Mediterranean Archaeology, 2024)
Interest in earthquakes in Mediterranean archaeology has distinct disciplinary origins. Since the inception of archaeoseismology—earthquake archaeology—in the 1980s, approaches to earthquake factors have been characterized by reliance on ancient historical sources. However, although texts have supported the identification of earthquake disasters in material destruction, documentary records extend far beyond particular events and experiences of disaster; diverse cultural perceptions of earthquakes as expressed in ancient textual sources also offer an alternative interpretation for Mediterranean archaeology. This study reviews the material-geological record of Helike in Greece—the victim of an infamous major earthquake in 373 BC—in order to assess the impact of seismic activity on the site from the third millennium BC to the fifth century AD. Evidence for such an impact includes archaeoseismic types of destruction, anti-seismic construction in architecture and stratigraphically associated soil micromorphological evidence of seismically triggered soft sediment deformation structures (SSDS). A reassessment of ancient accounts of the 373 BC event to explore Graeco-Roman cultural perceptions of earthquakes provides a new interpretive frame for the material-geological record of Helike. This alternative interpretation repositions earthquakes, traditionally perceived as ‘natural’ disasters implicated in ‘collapse’ and ‘catastrophe’, as social phenomena. The case of Helike demonstrates the value of documentary records for reframing the complex social and political dimensions of recurrent earthquakes and persistent geological hazards.